The Analysis of the Micro and Macro Fundamental, Ownership Structure, Good Corporate Governance and Capital Structure Effect on Financial Performance (Study of Manufacturing Companies Food and Beverage Sector Listed on the Indonesia Stock Exchange) - Hwihanus Hwihanus; Aisyah Dewi Ramadhani (Jurnal Ilmiah Akuntansi, 2019)
The research objective is to examine and analyze the influence of macro fundamentals, micro fundamentals, ownership structure, good corporate governance and capital structure on financial performance. This research is quantitative by using statistics in testing hypotheses. The research sample uses purposive sampling in 2013 - 2017. The method used in this study is Partial Least Square (PLS). Hypothesis testing shows that macro fundamentals have no significant effect on ownership structure and ownership structure has no significant effect on financial performance. Other tests accept the hypothesis that there is a significant influence between variables where financial performance is influenced by macro fundamentals, micro fundamentals, capital structure, financial structure, and GCG.